(untitled) (The Agriculturists, 2014)
An experiment was conducted at Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur during April 2013 to June 2013 to study the effect of three storage containers (tin container, polythene bag and cloth bag); and five storage periods (0, 15, 30, 45, and 60 days) on the seed quality of soybean. The experiment was laid out in Completely Randomized Design (CRD) with four replications. The soybean seeds stored in tin container showed maximum germination capacity with high germination index, highest seedling growth, seedling dry weight per plant and vigour index. The seeds stored in cloth bag had the lowest seed quality during the testing period. The highest 1000-seed weight, moisture content, electrical conductivity, abnormal seedlings and number of dead seeds were recorded in cloth bag; where the equivalent lowest values were recorded in tin container. The moisture content, 1000-seed weight, electrical conductivity, number of abnormal seedlings and dead seeds were increased with the longer period of storage. In addition, germination index, seedling growth, dry weight per plant of soybean seedling, and vigor index decreased with the increase in storage period. Among the three containers, tin container was the best and the cloth bag was the worst storage container for soybean seed storage for long period. DOI: http://dx.doi.org/10.3329/agric.v12i1.19585 The Agriculturists 2014; 12(1) 85-95